Understanding the effect of sustained use of cloud-based point of sales on SMEs performance during covid-19 pandemic - Yeney Widya Prihatiningtias; Maudina Rahma Wardhani (Universitas Hayam Wuruk Perbanas, 2021)
This study examined the effect of sustained use of cloud-based point of sales on SMEs’ performance during COVID-19 pandemic. In this study, both quantitative and qualitative approaches were employed. The sample consists of the food and beverage industries from Small and Medium Enterprises (SMEs) located in Malang City, Indonesia. The quantitative data which succeeded to collect 91 responses was taken from the questionnaire distribution of the sample SMEs and it was analyzed by using SPSS 21 with the multiple linear regression method, which indicated there is a relationship between sustained-use of cloud-based point of sale on SMEs non-financial performance during COVID-19 pandemic. 9 SMEs representatives, the owner, or the manager, were also interviewed to gain further insights and to confirm the quantitative findings. Technology Continuance Theory (TCT) was used to explain the link between the sustained use of cloud-based point of sale on SMEs’ performance during the COVID-19 pandemic. However, the results from both approaches found that there is a positive relationship between sustained use of cloud-based point of sale on SMEs non-financial performance during COVID-19 pandemic and the relationship between sustained use of cloud-based point of sale on SMEs financial performance is negative.